Pharmacist interventions in an public emergency hospital service of Porto Alegre classify according Pharmaceutical Care Network Europe (PCNE) Association Classification for Drug Related Problems - Tauchert Rossato, Patrick; Hepp Schwambach, Karin; Becker, Matheus William; Blatt, Carine Raquel (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: To analyze the records of pharmaceutical interventions of a public hospital and clas sify them using the Pharmaceutical Care Network Europe (PCNE) Association Classification for Drug-Related Problems. Methods: Descriptive and retrospective study, based on a data base of records of pharmaceutical interventions performed in 2022 by the Clinical Pharmacy service of a public emergency care hospital. The interventions were quantified and classified according to the service standards and then reclassified according to the standards of the classification for drug-related problems of the PCNE version 9.1. Results: During 2022, 414 pharmaceutical interventions related to 337 patients were recorded. Regarding the location, the interventions were performed on patients admitted to the clinical inpatient unit (35%), intensive care unit (33%), emergency room (27%), and surgical recovery room (5%). Accor ding to the service’s own classification, reconciliation of health information (36%) and dose or frequency adjustment (33%) were the most frequent pharmaceutical interventions. Using the PCNE system to classify pharmaceutical interventions, the main problems identified were: effectiveness (86%) and safety of treatment (7%); the main causes were: dose selection (36%) and patient transfer (37%); and the main type of intervention: related to the prescriber (91%). Conclusions: The PCNE classification can be used in a hospital environment to generate qua lity indicators that allow the evaluation of processes and results related to pharmaceutical interventions. Research is needed that uses standardized methods to evaluate outcomes and events, allowing comparison between results.